Biased Decoding and the Foundations of Communication - Luca Braghieri (Center for Economic Studies and ifo Institute (CESifo), 2023)
One-way communication between an informed sender and an uninformed receiver involves two fundamental processes: a process of encoding – whereby the sender maps states of the world or concepts into arbitrary signals – and a process of decoding – whereby the receiver makes inferences about the state of the world conditional on each signal realization. In this paper, I develop machinery to study the process of decoding for an agent who might have inaccurate beliefs about the information environment (a biased decoder) and show how such machinery can help shed light on foundational aspects of communication.
Keywords: 330